Investigation of The Effect of Using Whole Wheat Flour and Different Additives in Bread Kadayif on Acrylamide and Hydroxymethyl Furfural (HMF) - Kimya Seyyedcheraghi; Halis Gürbüz Kotancılar; Pınar Civelek (Food Science and Engineering Research, 2024)
In this study, it has been experimentally investigated to add nutritional and functional properties to bread kadayif, which is a local product, with the addition of whole flour, and to reduce the content of acrylamide and HMF, which may occur as a result of some reactions, with the application of heat treatment in bread kadayif. For this purpose, 3 different additives (L-cysteine, citric acid, NaHCO3) and 2 different ratios (0 and 30%) whole flour were added to the bread kadayif formulation at 3 different rates (0, 1.5% and 3%). At the end of production, the samples were subjected to acrylamide and HMF analyzes as well as viscosity, pH, aw, moisture, color and sensory analyzes. 3 additives (L-cysteine, citric acid, NaHCO3) added to the bread kadayif dough caused an increase in acrylamide level in the samples without whole flour compared to the control. In the samples using whole flour, 3 additives added to the formulation provided a decrease in acrylamide levels compared to the control. In HMF content, L-cysteine and NaHCO3 decreased the amount of HMF in samples without and with whole flour added to the formulation compared to the control, while citric acid caused an increase in HMF content compared to the control. When we evaluated the sensory analysis results, increasing the level of whole flour caused a decrease in outer appearance, interior color, taste and smell values. The most appreciated outer appearance, interior color, taste, odor, aroma, texture, mouthfeel and general acceptability values were observed in the citric acid additive.